1999
DOI: 10.1007/s005950050641
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative brain complications following retrograde cerebral perfusion

Abstract: This study was undertaken to investigate the neurological risk factors associated with the retrograde cerebral perfusion (RCP) technique, by examining the relationship between intraoperative parameters and post-operative brain complications. A total of 12 patients who underwent surgery for thoracic aortic aneurysms using the RCP technique were included in this study. Profound hypothermia was induced through cardiopulmonary bypass which was established with a femoral arterial cannula and bicaval return. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[1][2][3][4] Thourani et al 2 reported the incidence of the perioperative neurological complications to be more frequent in diabetic patients than in patients without diabetes. However, the precise mechanisms of postoperative cognitive dysfunction in diabetic patients after cardiac surgery are still not fully understood.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3][4] Thourani et al 2 reported the incidence of the perioperative neurological complications to be more frequent in diabetic patients than in patients without diabetes. However, the precise mechanisms of postoperative cognitive dysfunction in diabetic patients after cardiac surgery are still not fully understood.…”
Section: Introductionmentioning
confidence: 98%
“…However, the precise mechanisms of postoperative cognitive dysfunction in diabetic patients after cardiac surgery are still not fully understood. [1][2][3][4] The possible mechanisms of postoperative cognitive dysfunction are cerebral ischemia or cerebral desaturation due to hypoperfusion during cardiopulmonary bypass (CPB). 1,5,6 Croughwell et al 6 reported that lower values for internal jugular venous oxygen hemoglobin saturation (SjvO 2 ) at the end of rewarming were associated with cognitive deficits at 4-8 days after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…10 In both of these studies, cerebral edema was not detected as it was in the previous dog model. Still, another adult study by Sato et al 11 found a negative correlation between SVC pressure during RCP for thoracic aortic aneurysm repair and delayed emergence from anesthesia. Interestingly, the SVC pressures in this study had a mean of 159/6 mmHg and no patient exceeded 23 mmHg.…”
Section: Discussionmentioning
confidence: 95%
“…This method has advantages over conventional techniques, because it helps maintain uniform hypothermia by using a different method of perfusate administration. It also has a mechanism of oxygen and metabolic substrate supply, and acts in the removal of toxic metabolites and carbon dioxide, in addition to preventing cerebral embolization with air, atheromatous plaques, thrombi or other cell and tissue debris 43 .…”
Section: Strategies For Brain Protectionmentioning
confidence: 99%